1993
DOI: 10.1016/0270-9139(93)90508-k
|View full text |Cite
|
Sign up to set email alerts
|

Prior esophageal variceal bleeding does not adversely affect survival after orthotopic liver transplantation

Abstract: Prior variceal bleeding may adversely affect the prognosis of orthotopic liver transplantation. We studied this question by evaluating all 175 adult patients undergoing orthotopic liver transplantation at our institution to determine risk factors associated with mortality after transplantation. Seventy patients demonstrated prior variceal bleeding, and of those, 32 had a course of sclerotherapy. Thirteen also had portal systemic shunts. Compared with the 105 transplant patients who had no prior bleeding, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the survival rate of the 19 unrandomized patients who underwent LT was 89% after 30 days and 53% after 5 years, which was not significantly different from the survival rates for LT reported by UNOS. PCS did not increase the mortality rate or complications of subsequent LT. Added to the data from our study are at least 10 reports of retrospective studies in the literature that concluded that portosystemic shunts do not affect the results of subsequent LT [5][6][7][43][44][45][46][47][48][49][50][51]. That conclusion has not been contradicted by reported studies.…”
Section: Discussionmentioning
confidence: 55%
“…However, the survival rate of the 19 unrandomized patients who underwent LT was 89% after 30 days and 53% after 5 years, which was not significantly different from the survival rates for LT reported by UNOS. PCS did not increase the mortality rate or complications of subsequent LT. Added to the data from our study are at least 10 reports of retrospective studies in the literature that concluded that portosystemic shunts do not affect the results of subsequent LT [5][6][7][43][44][45][46][47][48][49][50][51]. That conclusion has not been contradicted by reported studies.…”
Section: Discussionmentioning
confidence: 55%